PENGARUH PELAKSANAAN PROMOSI JABATAN TERHADAP SEMANGAT KERJA KARYAWAN DIVISI REDAKSI PADA PT. TRIBUN PEKANBARU - Rezki Ramadhanni; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at PT. Tribun Pekanbaru.arrangementof the problem is the influence of the influence of the implementation of a promotion to employee morale editorial division at PT. TribunPekanbaru.purposeof this study is to investigate the implementation of promotions , morale , and determine the effect the implementation of a promotion to employee morale editorial division of PT . Tribun Pekanbaru .The author uses quantitative descriptive analysis method .Collecting data using kuisioner.Sampel used is sensus.Sumber data used are primary data or data obtained directly from the object of study , and secondary data is data collected author of PT . Tribun Pekanbaru.The results showed that the implementation of the promotion has a significant impact on employee morale editorial division of PT . Tribun Pekanbaru .Keywords : the implementation of the promotion , morale , editorial division